Informatics competencies essential to decision making in nursing management - Jensen, Rodrigo [UNESP]; Guedes, Erika de Souza; Januario Leite, Maria Madalena (Univ Sao Paolo, 2016)
Objective: To identify informatics abilities essential to decision making in nursing management. Method: Survey study with specialist nurses in health informatics and management. An electronic questionnaire was built based on the competencies Information Literacy (five categories; 40 abilities) and Information Management (nine categories; 69 abilities) of the TIGER - Technology Informatics Guiding Education Reform - initiative, with the guiding question: Which informatics abilities are essential to decision making in management? Answers were sorted in a Likert scale, ranging from 1 to 5. Rasch analysis was conducted with the software WINSTEPS (R). Results were presented in logits, with cutoff value zero. Results: Thirty-two specialists participated, coming from all regions of Brazil. In the information literacy competency, 18 abilities were considered essential and in Information Management, 38; these were sorted according to their degree of essentiality. Conclusion: It is believed that the incorporation of these abilities in teaching can support the education of nurse managers and contribute to evidence-based practice, incorporation of information and communication technologies in health and information management.
Keywords: Nursing Informatics; Nursing Administration Research; Competency-Based Education